Cognitive deficits in Parkinson's disease - van Spaendonck, K P; Berger, H J; Horstink, M W; Cools, A R (Tijdschrift voor gerontologie en geriatrie, 1998)
In neuropsychological studies of Parkinson's disease, cognitive deficits are frequently reported, but the nature of these deficits is not clear. As far as cognitive deficits are manifest in parkinsonian patients at an early stage of the disease, many studies tend to describe them as fitting a frontal syndrome. As a consequence of dysfunction of the striatum, the (pre)frontal cortex receives deficient input from the striatum, which might explain the similarity of the cognitive deficits of parkinsonian patients with those of patients with frontal dysfunction. The present studies provide evidence that the cognitive deficits of parkinsonian patients display a certain similarity with those of patients with frontal dysfunction at the level of the ultimate performance, but that the underlying processes have a distinct character. Parkinsonian patients exhibit a decrease in self-generated problem-solving. This deficit is manifest at a level of cognitive function, which goes beyond task or domain. Among all disease variables, only severity of the disease and especially rigidity proved to be related consistently to this decrease in self-generated problem-solving.